Transnational Education Redefined - Wilkins, Stephen; Huisman, Jeroen (International Higher Education, 2025)
As existing definitions of transnational education (TNE) specify that an institution or educational program has to cross national borders, some providers commonly perceived to operate in the TNE field are excluded. Country-branded universities (CBUs) do not cross borders, but they borrow or transfer elements of their affiliated country’s higher education system, including that country’s culture and values. We offer a broader, more encompassing definition of TNE that includes more diverse forms of provider.